Developing intercultural awareness from short-term study abroad: insights from an interview study of Japanese students. (4th March 2021) - Humphreys, Gareth; Baker, Will
ABSTRACT: Developing intercultural awareness among participants is an objective of many short-term study abroad (SA) programmes. However, such programmes often focus on essentialist 'target' national culture learning. Moreover, simplistic evaluation of intercultural development risks the decontextualisation of personally meaningful learning in experiences abroad. This qualitative interview study investigated intercultural development, conceptualised through intercultural awareness (ICA), among 15 students who took part in programmes in diverse locations. Thematic analysis revealed varying experiences and highlighted the importance of multilingual and multicultural programmes for meaningful ICA development. Preparation for short-term SA needs to recognise linguacultural diversity and move away from essentialist target culture learning.